War dance [videorecording (DVD)] - Fine, Sean; Nix Fine, Andrea (Thinkfilm, LLC ; distributed by Image Entertainment, 2008)
A depiction of the transformative and uplifting potential of music and dance in the lives of children. Dominic, Rose, and Nancy are three children of the Acholi tribe, living in the war zone displacement camp in Patongo, Uganda. As war refugees, their families have been decimated, their homes lost, and they have been burdened with vivid memories of violence. However, the children are at least able to attend a camp school that offers them inspiration, as they participate in music, song and performance. When they are invited to compete in an annual music and dance festival in their nation's capitol, an opportunity for which all 20,000 Ugandan schools compete, they are given the chance to regain hope and success in their lives.